2022
DOI: 10.3390/nu14163444
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Replacement Therapy in Chronic Kidney Disease Patients

Abstract: (Background) The aim of our study was to evaluate the efficacy and safety of testosterone replacement therapy (TRT) in men with chronic kidney disease and hypogonadism on conservative and hemodialysis treatment. (Methods) The studied population consisted of 38 men on hemodialysis (HD), 46 men with CKD stages II-IV (predialysis group, PreD) and 35 men without kidney disease who were similar in age to others (control group). Serum total testosterone level (TT) was measured, and free testosterone level (fT) was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In recent years, some single-center research institutions have attempted to use TRT to observe whether it can improve the prognosis of CKD and reduce the incidence of complications. For example, according to Skiba et al [ 3 ], TRT administration in CKD patients undergoing dialysis or predialysis significantly improved clinical symptoms of hypogonadism and erectile dysfunction. Yeo et al [ 27 ] found that grip strength significantly improved and quality of life improved markedly after TRT in a retrospective study on CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some single-center research institutions have attempted to use TRT to observe whether it can improve the prognosis of CKD and reduce the incidence of complications. For example, according to Skiba et al [ 3 ], TRT administration in CKD patients undergoing dialysis or predialysis significantly improved clinical symptoms of hypogonadism and erectile dysfunction. Yeo et al [ 27 ] found that grip strength significantly improved and quality of life improved markedly after TRT in a retrospective study on CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In males, this manifests as erectile dysfunction, while in females it leads to menstrual irregularities and decreased fertility due to steroid hormone secretion disruption, especially testosterone deficiency [ 2 ]. Testosterone replacement therapy (TRT) has been shown to alleviate hypogonadism in CKD patients [ 3 ], and males with low testosterone levels are at a significantly greater risk for developing CKD than those with normal testosterone levels [ 4 ]. Testosterone plays an important role in improving alertness and physical performance, enhancing libido, increasing muscle strength, and boosting the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…randomly divided anemic dialysis patients into two groups: the first group received three times weekly erythropoietin whereas the second group was given equal doses of erythropoietin in addition to nandrolone decanoate weekly. Hemoglobin levels were improved in both groups but were significantly better in the second group [ 39 , 40 ]. The impact of testosterone supplementation in HD patients was also investigated by Teruel et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, hypogonadal males with diabetes have a higher plaque score, coronary artery disease, and cardiovascular mortality risk [ 13 , 14 ], which might be due to hyperlipidemia induced by lower androgen levels [ 15 ]. Additionally, hypogonadism is also associated with chronic kidney disease which mainly occurs as a consequence of diabetes [ 16 , 17 ]. Therefore, it is important to study reproductive disorders caused by diabetes because it might be associated with damage caused to other systems as well.…”
Section: Introductionmentioning
confidence: 99%